An investigation into the mechanisms underlying the Plant Growth Promoting Properties of G. diazotrophicus - Pallucchini, Michele (2024)
The indiscriminate use of synthetic nitrogen fertilisers to support intensive farming in the last decades has been one of the leading causes of soil degradation, greenhouse gases emission, eutrophication and ecosystem unbalance. Plant growth promoting bacteria (PGPB) have the potential to alleviate this environmental damage by providing a more sustainable alternative for enhancing crop productivity, but require careful optimisation as their physiology remain elusive. In this study, the PGP activity of the non-nodule forming diazotroph Gluconacetobacter diazotrophicus was assessed in monocot and dicot systems through the comparison of different inoculation strategies and experimental setups. In particular, two of the main contributors to the PGP capability of this bacterium, i.e., nitrogen fixation and hormonal production, were investigated through the use of mutants and gene expression analyses, and were further evaluated in relationship to the bacterial colonisation dynamic under different nutrient conditions. The study unveiled a multifaceted root invasion strategy, encompassing root hair colonisation, crack entry, and the ability for intracellular invasion and cytoplasmic transmission, followed by the migration into the shoot through xylem vessels and the occupation of stomata and trichomes. A complex and delicate balance between bacterial PGP factors and the carbon and nitrogen metabolism was uncovered. The presence of ammonium in the system had a negative impact on the PGP effect, while the lack of a nitrogen source highlighted the beneficial bacterial stimulation, although the bacterium itself was not sufficient for normal plant development. Bacterial genes responsible for hormonal production were expressed during early symbiosis stages in the root system of plants grown in nitrogen-replete conditions; as time progressed, nitrogen fixation genes were upregulated, primarily in the aerial parts of the plant, while the bacterial genes conferring protection against the plant’s immune response were switched off as the symbiosis established. The introduction of an external carbon source enhanced the expression of nitrogen fixation genes in planta. These findings may have a potential implication on the application strategies in agricultural settings. Furthermore, novel tools for genetic manipulation and metabolic engineering of Gluconacetobacter diazotrophicus are described.